Preparation of Noble Metal Nanoparticles and Their Application in Photocatalytic Water Splitting - Su, Rongjia (Transactions on Environment, Energy and Earth Sciences, 2026)
Photocatalytic water splitting represents a sustainable method to the production of hydrogen, leveraging sunlight to drive the dissociation of water molecules into hydrogen and oxygen through the semiconductor photocatalysts enhanced by noble metal nanoparticles. This paper will explore the fundamental principles of photocatalysis, including energy band theory and the critical role of noble metals such as platinum, gold, palladium, and silver in facilitating electron transfer, reducing recombination, and improving catalytic efficiency. Key synthesis methods for noble metal nanoparticles, including chemical reduction, hydrothermal, and environmentally friendly approaches are discussed, emphasizing factors like particle size, shape, and surface modifications that influence its performance and stability. Applications in systems like CdS-based catalysts and phosphorus-modified palladium nanoparticles demonstrate significant enhancements in the rate of hydrogen evolution, with comparisons that highlight the trade-offs between activity, cost, and endurance. Challenges such as photocorrosion and electron-hole recombination are analyzed, alongside synergistic effects from plasmonic properties and multi-metal configurations. The discussion underscores the potential of optimized noble metal systems for efficient, large-scale hydrogen generation, while identifying future directions for improved stability and visible light utilization to advance clean energy technologies.
Keywords: Photocatalytic water splitting; noble metal; nanoparticles.